Naming Institutionalized Racism in the Public Health Literature: A Systematic Literature Review. (May 2018) - Hardeman, Rachel R.; Murphy, Katy A.; Karbeah, J'Mag; Kozhimannil, Katy Backes
Objectives: Although a range of factors shapes health and well-being, institutionalized racism (societal allocation of privilege based on race) plays an important role in generating inequities by race. The goal of this analysis was to review the contemporary peer-reviewed public health literature from 2002-2015 to determine whether the concept of institutionalized racism was named (ie, explicitly mentioned) and whether it was a core concept in the article. Methods: We used a systematic literature review methodology to find articles from the top 50 highest-impact journals in each of 6 categories (249 journals in total) that most closely represented the public health field, were published during 2002-2015, were US focused, were indexed in PubMed/MEDLINE and/or Ovid/MEDLINE, and mentioned terms relating to institutionalized racism in their titles or abstracts. We analyzed the content of these articles for the use of related terms and concepts. Results: We found only 25 articles that named institutionalized racism in the title or abstract among all articles published in the public health literature during 2002-2015 in the 50 highest-impact journals and 6 categories representing the public health field in the United States. Institutionalized racism was a core concept in 16 of the 25 articles. Conclusions: Although institutionalized racism is recognized as a fundamental cause of health inequities, it was not often explicitly named in the titles or abstracts of articles published in the public health literature during 2002-2015. Our results highlight the need to explicitly name institutionalized racism in articles in the public health literature and to make it a central concept in inequities research. More public health research on institutionalized racism could help efforts to overcome its substantial, longstanding effects on health and well-being.